The Impact of Cannabis Use on Clinical Outcomes in Recent Onset Psychosis - Barrowclough, Christine (Schizophr Bull, 2015)
Background: There are inconsistencies in findings as to whether cannabis use has a negative impact on clinical outcomes for people with established psychosis. Effects may be more evident on patients with recent onset psychosis. Aim: To investigate the relationship between cannabis use and clinical outcome, including whether change in cannabis use affects psychotic symptoms, affective symptoms, functioning and psychotic relapse in a sample of people in early psychosis with comorbid cannabis abuse or dependence. Methods: One hundred and ten participants were examined prospectively with repeated measures of substance use antecedent to psychopathology at baseline, 4.5, 9, and 18 months. We used random intercept models to estimate the effects of cannabis dose on subsequent clinical outcomes and whether change in cannabis use was associated with change in outcomes. Results: There was no evidence of a specific association between cannabis use and positive symptoms, or negative symptoms, relapse or hospital admissions. However, a greater dose of cannabis was associated with subsequent higher depression and anxiety. Change in the amount of cannabis used was associated with statistically significant corresponding change in anxiety scores, but not depression. Additionally, reductions in cannabis exposure were related to improved patient functioning. Conclusions: Reducing cannabis may be directly associated with improvements in anxiety and functioning, but not other specific symptoms.